Independent variation of avian sensitivity to climate change and trait-based adaptive capacity along a tropical elevational gradient - Nowak, Larissa (2022)
Aim: How species respond to climate change is influenced by their sensitivity to climatic conditions (i.e. their climatic niche) and aspects of their adaptive capacity (e.g. their dispersal ability and ecological niche). To date, it is largely unknown whether and how species’ sensitivity to climate change and their adaptive capacity covary. However, understanding this relationship is important to predict the potential consequences of a changing climate for species assemblages. Here, we test how species’ sensitivity to climate change and trait-based measures of their ecological adaptive capacity (i) vary along a broad elevational gradient and (ii) covary across a large number of bird species. Location: A Neotropical elevational gradient (300–3600 m.a.s.l.) in the Manú Biosphere Reserve, south-east Peru. Methods: We focus on 215 frugivorous bird species along a Neotropical elevational gradient. We approximate species’ sensitivity to climate change by their climatic niche breadth, based on species occurrences across South America and bioclimatic variables. In addition, we use a trait-based approach to estimate the dispersal ability of species (approximated by their wing pointedness), their dietary niche breadth (approximated by bill width) and their habitat niche breadth (the number of used habitat classes). Results: We found that (i) species’ climatic niche breadth increased with elevation, while their trait-based dispersal ability and dietary niche breadth decreased with elevation, and (ii) sensitivity to climate change and trait-based adaptive capacity were not related across species. Main conclusions: These results suggest different mechanisms of how species in lowland and highland assemblages might respond to climate change. The independent variation of species’ sensitivity to climate change and their trait-based adaptive capacity suggests that accounting for both dimensions will improve assessments of species’ susceptibility to climate change and potential impacts of climate change on diverse species assemblages.